Acentolândia : criação e aplicações de um jogo de regras sobre acentuação gráfica para séries iniciais do ensino fundamental - Cezar, Kelly Priscilla Lóddo (2009)
Research findings and official data reveal a low learning performance of several school subjects and warn of the importance of alternative methodologies in order to meet the didactic needs of the education system such as the use of rule games. This dissertation aims at describing the design of a rule game upon the accent mark subject-matter in mother tongue - Accentland as well as following and assessing its applications by using the findings in order to make the necessary changes and improve it. Three game applications were conducted with intervention sessions which consisted of 4th and 5th-graded students of primary school enrolled in state schools in Maringá, Paraná. The data collection of the three rule game applications was performed in four steps: diagnosis of the writing performance; application of a pre test and a clinical interview concerning the subject that was focused in the pedagogical intervention; pedagogical intervention accomplishment; and new application of a test and clinical interview. The findings of this experimental research evidenced the hypothesis that students improve on the accent mark activities when the pedagogical intervention is performed with the use of the Accentland game. It happens both quantitatively - improvement of the performance of accent mark in single words - and qualitatively - explanation and justifications of the orthographic rules.